Answer:
92
Step-by-step explanation:
Answer:
1
Step-by-step explanation:
Column A=X the first value for x is 1
Column B has the x value replaced in the equation 5x+8. 5(1) + 8
Column C has the result, y=13
Remark
What this is telling you to do is put 3x + 3 in the question wherever there was an x to start with.
Solution
f(x) = -3x + 4
f(3x + 3) = - 3(3x + 3) + 4
f(3x + 3) = -3*3x + (-3)*(3) + 4
f(3x + 3) = - 9x - 9 + 4
f(3x + 3) = -9x - 5 <<<<< Answer
Answer:
32 n
Step-by-step explanation:
I had the same problem but I used a net force calculator the formula is F=MA so it would be 32=16/2.0 :)
Answer:
in my opinion anush has the better performance